Lifestyle influences on airway health in children and young adults - Rosenkranz, Sara K. (Kansas State University, 2010)
The overall aim of this dissertation was to ascertain the influences of lifestyle factors on airway health in children and young adults. In Study 1 (Chapter 2) the effect of a high-fat meal on airway inflammation and hyper-responsiveness was examined. Results revealed a post-prandial increase (p<0.05) in total cholesterol (~4%), triglycerides (~93%), and exhaled nitric oxide (a marker of airway inflammation, ~19%) two-hours following a high-fat meal (74.2±4.1g fat). These novel findings suggest that a high-fat meal may contribute to impaired airway function. In study 2 (Chapter 3) we assessed the role of body fat and physical activity (PA) on airway health in prepubescent children. This study revealed that children with higher-body-fat levels (>21%), who were not meeting current PA recommendations, experienced greater (p<0.05) amounts of post-exercise airway narrowing (FEV1, forced expiratory volume in 1-second, ~11%), as compared to children with lower-body-fat (<21%), who were meeting PA guidelines. These findings suggest that elevated adiposity and low PA levels may place children at risk for development of asthma and asthma-like symptoms. In study 3 (Chapter 4), based on study 2 results, we assessed the impact of 8 weeks of high-intensity interval training on airway health in children who were not meeting PA guidelines. We determined that high-intensity training significantly increased V02max (~24%), and decreased total cholesterol (~11%) and LDL cholesterol (~35%). Additionally, we found improvements (p<0.05) in ∆FEV1 both post-exercise (pre: -7.6±2.2%, post: -1.3±1.8%) and post-eucapnic voluntary hyperventilation (pre: -6.7±2.2%, post: -1.4±1.5%) with training. Further, Lower-body-fat and higher V02max subjects experienced significantly greater improvement in ∆FEV1 following training than higher-body-fat and lower V02max subjects (r=-0.80, r=0.73, respectively). These results suggest that in children, high-intensity training can ameliorate the negative health consequences of inactivity. However, increased body fat, and low V02max levels may constrain these improvements. This series of studies underscores the importance of dietary habits, body composition, and PA for airway health in children and young adults. These findings may be useful in determining policies and practices impacting children’s health, and could facilitate protocol development for prevention of asthma-like symptoms.
Keywords: hyper-responsiveness; airway health; children; physical activity; airway inflammation; high-intensity training; Health Sciences, General (0566); Health Sciences, Nutrition (0570)